Effect of lipegfilgrastim administration as prophylaxis of chemotherapy-induced neutropenia on dose modification and incidence of neutropenic events: real-world evidence from a non-interventional study in Belgium and Luxembourg. Issue 1 (2nd January 2021) - Fontaine, Christel; Claes, Nele; Graas, Marie-Pascale; Samani, Khalil Kargar; Vuylsteke, Peter; Vulsteke, Christof
ABSTRACT: Objectives : This study evaluated the effect of lipegfilgrastim, a glycopegylated granulocyte-colony stimulating factor, used as primary (PP) or secondary prophylaxis (SP) on chemotherapy (CT) treatment modifications, as well as the incidence of CT-induced neutropenic events in adult patients receiving cytotoxic CT with or without biological therapy (BT) for solid and hematological tumors, in routine clinical practice. Other objectives were to characterize the population of lipegfilgrastim-treated cancer patients and safety assessment. Methods : This phase 4, prospective, observational study was conducted at 15 centers from Belgium and Luxembourg, between 2015 and 2017. Results : Of 139 patients, 82.7% had breast cancer and 54.7% were treated with dose-dense regimens. Most received lipegfilgrastim as PP (82.0%) and were at high-risk of febrile neutropenia (FN) (68.3%). FN and grade III/IV neutropenia were reported for 7.9% and 22.3% patients. Among 123 evaluated patients, CT/BT dose modifications were recorded for 33.3% (PP) and 52.4% (SP) of patients receiving lipegfilgrastim; dose reductions, followed by dose delays, were more frequent than omissions. Among 45 patients with dose modifications, FN was reported for 8.8% and 9.1% patients and grade IV neutropenia for 17.6% and 18.2% of patients when lipegfilgrastim was applied for PP and SP, respectively. Adverse events related to lipegfilgrastim occurred for 55 (39.6%) patients; bone pain and back pain were more frequent. Lipegfilgrastim-related serious adverse events were reported for 9 (6.5%) patients. Conclusion : Use of lipegfilgrastim in real-world settings resulted in limited CT dose modifications and low incidences of neutropenic events, with no new safety concerns arising. Graphical Abstract: